Pengembangan Model Bisnis Tentang Telekomunikasi di Perusahaan Berdasarkan Perspektif Pelanggan - Zoellys Fix Nurfadholi (Sekolah Tinggi Maritim Yogyakarta, 2020)
Telecommunications has become a necessity in every activity. Based on the results of the publication of the Central Statistics Agency (2018) the number of cellular telephone subscribers in Indonesia reached 319.4 million. Based on this number there is a large market potential because it can be assumed that each customer requires at least one telephone number, and each number is required to be used for telecommunications costs such as monthly bills for postpaid number customers and phone credit for prepaid number customers. Telecommunications needs not only occur at the individual level but also in an organizational environment such as the company which will later be used as the main target market in the business model. The large market potential gave rise to the idea to create a business concept that focuses on the company's customer segment that is able to provide convenience, security, flexibility, and transparency so as to facilitate the company's business activities and reduce the risk of loss due to misused communication benefits.